Design and manufacturing of the Linko demountable fabric pavilion for the motorsport sector - Beccarelli, Paolo; Maffei, Roberto (Elsevier, 2016)
This paper offers a detailed overview of the design and manufacturing aspects faced during the design and construction of the temporary pavilion for Linko Resources Ltd. The pavilion has been designed for the motorsport season 2015 and is based on bent aluminium profiles, designed to minimize the weight of the structures, and a double membranes skin realized through a PU coated Polyester fabric (waterproof layer) and a PVC coated polyester open mesh fabric (solar radiation control). The first section of the paper describes the requirements of the client, the architectural design and the structural design of the components. The second section presents the materials used, the connections and the optimization of the packaging in order to minimize the transportations volumes.